2008
DOI: 10.1177/0149206308316058
|View full text |Cite
|
Sign up to set email alerts
|

Organizational Ambidexterity: Antecedents, Outcomes, and Moderators

Abstract: Organizational ambidexterity, defined as an organization's ability to be aligned and efficient in its management of today's business demands while simultaneously being adaptive to changes in the environment, has gained increasing interest in recent years. In this article, the authors review various literature streams to develop a comprehensive model that covers research into the antecedents, moderators, and outcomes of organizational ambidexterity. They indicate gaps within and across different research domain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

65
1,964
4
44

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 1,879 publications
(2,193 citation statements)
references
References 146 publications
65
1,964
4
44
Order By: Relevance
“…Therefore the flexibility of these arrangements and how they operate across all levels of the collaborationfrom the project(s) to the 'organisation' or network as a whole -will help explain a collaboration's ability to ensure appropriately resourced activity and the capacity to respond to wider issues and pressures as they arise. It has been suggested that an organisation's ambidexterity, that is its ability to be aligned and adapt to demands, has been found to be a prerequisite of organisational survival and success, 121 and arguably for its resilience too. The way in which concepts such as these might transfer to a 'constellation of interconnected practices' 122 such as CLAHRCs, is in their potential to explain how these networks evolve and then sustain themselves (or not).…”
Section: Discussion Conclusion and Implicationsmentioning
confidence: 99%
“…Therefore the flexibility of these arrangements and how they operate across all levels of the collaborationfrom the project(s) to the 'organisation' or network as a whole -will help explain a collaboration's ability to ensure appropriately resourced activity and the capacity to respond to wider issues and pressures as they arise. It has been suggested that an organisation's ambidexterity, that is its ability to be aligned and adapt to demands, has been found to be a prerequisite of organisational survival and success, 121 and arguably for its resilience too. The way in which concepts such as these might transfer to a 'constellation of interconnected practices' 122 such as CLAHRCs, is in their potential to explain how these networks evolve and then sustain themselves (or not).…”
Section: Discussion Conclusion and Implicationsmentioning
confidence: 99%
“…Scholars indicate that contextual factors such as senior team integration helps in balanced resource allocation, forms cross-fertilization and synergies towards ambidextrous activities (e.g., Jansen et al 2008), and the ambidexterity performance link is also suggested to be the outcome of contextual variables and it is positively related to performance (Junni et al, 2013). The ability of the senior leadership teams to adopt to conflicting demands between old and new activities is a key indicator of organization success , and ambidexterity requires leaders with stock of behavioural skills (Raisch & Birkinshaw, 2008).…”
Section: Leadership and Ambidexteritymentioning
confidence: 99%
“…This introduces a particular type of leadership challenge, as managers must confront and overcome both personal and organizational needs for consistency (Eisenhardt & Brown, 1997;O'Reilly & Tushman, 2013;Smith & Tushman, 2005). Senior executives, in particular, are regarded as playing an important role in helping organizations to attend to contradictory demands and to foster ambidexterity (see, for example, Birkinshaw & Gupta, 2013;Gibson & Birkinshaw, 2004;Lubatkin, Simsek, Ling, & Veiga, 2006;O'Reilly & Tushman, 2011;Raisch & Birkinshaw, 2008;Smith & Tushman, 2005). Rather than attempting to align and resolve the conflicting demands of exploration and exploitation, executive leaders need to embrace divergence and build the capacity to attend simultaneously to competing and conflicting demands (Smith & Lewis, 2011), combining the attributes of rigorous cost cutters and of freethinking entrepreneurs (O'Reilly & Tushman, 2013;Tushman & O'Reilly, 1996).…”
Section: Ambidexterity Strategiesmentioning
confidence: 99%